Interest of Grade VIII Junior High School Students in Badminton at Barunawati 3 Junior High School North Jakarta - Rizal, Muhammad; Khaeroni; Iwan Setiawan (Enigma Institute, 2023)
The purpose of this study was to determine the level of interest of grade VIII Junior High School students in badminton at Barunawati 3 Junior High School North Jakarta. This research is a quantitative descriptive research with a survey method. The research population and sample were grade VIII students at Barunawati 3 Junior High School North Jakarta, with a total of 106 students. Furthermore, data collection was collected by giving instruments to respondents. The instrument used was a questionnaire with a total of 31 questions. Validation of this instrument uses a content validity test. The data analysis used is a descriptive statistical analysis by translating the research results into scores and percentages. Based on the results of the research and discussion, it can be concluded that students' identification of great interest in badminton at Barunawati 3 Junior High School North Jakarta tends to be in the low category. These results are shown in the following details. The very high category was 10.7%, followed by the high category at 37.9%, then the low category at 47.1%, and the very low category at 4.3%. The results of the research carried out were based on indicators from internal and external factors as a reference for identifying students' interest in participating in badminton so as to obtain these results.